RESPON PERTUMBUHAN DAN HASIL DUA VARIETAS KACANG PANJANG (Vigna sinensis L.) DENGAN BERBAGAI KONSENTRASI BIOSAKA - Andriani, Dewi; Izwar; Jekki Irawan; Nhyra Kamala Putri; Marzati (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2025)
Long bean is a vegetable from the legume family that is rich in protein, vitamins, minerals, and dietary fiber. This study aims to determine the growth and yield response of two long bean varieties to different biosaka concentrations. The study used a two-factor Randomized Block Design with interaction. The first factor consisted of two long bean varieties: V1 = Fagiola IPB Variety, and V2 = Parade Tavi, while the second factor was the biosaka concentration (B), which included three levels: B0 = 0 ml, B1 = 30 ml/l, and B2 = 60 ml/l. The results showed that the Parade Tavi variety and Fagiola IPB variety only significantly differed in the fresh weight per sample, while the biosaka concentration significantly affected the stem diameter. The Parade Tavi variety at the first harvest, 45 days after planting (DAP), had a stem diameter of 5.08 mm, fruit length of 32.12 cm, fresh weight per sample of 2.68 g, dry weight per sample of 0.48 g, and fresh weight per plot of 527.33 g. Meanwhile, the 60 ml/l biosaka concentration at the first harvest, 45 DAP, had a stem diameter of 5.62 mm, fruit length of 32.49 cm, fresh weight per sample of 2.79 g, dry weight per sample of 0.49 g, and fresh weight per plot of 532.33 g. These average values were relatively better compared to the Fagiola IPB variety and the 30 ml/l biosaka concentration. However, no interaction was found between the varieties and biosaka concentrations for all observed parameters.